Indentured Servitude in the 17th Century English Atlantic: A Brief Survey of the Literature. Issue 10 (6th October 2013) - Donoghue, John
<x xml:space="preserve">Abstract</x> This article surveys the literature on indentured servitude in the 17th century English Atlantic. It gives special attention to the recent challenge that Christopher Tomlins' celebrated book, Freedom Bound: Law, Labor, and Civic Identity in English Colonization, 1580–1865 (2010) has presented to widely accepted interpretations of unfree labor in colonial America. Within this context, the review canvasses three major themes in servant scholarship: servant migration, the laws of servitude, and servitude's relationship to slavery. A discussion of the scholarship that takes an Atlantic perspective on servitude within the wider history of colonization and colonial law reveals several problems with Tomlins' exclusive focus on North America. Tomlins could also have radically strengthened his already illuminating view of servant law as a foundation of slavery by engaging with work on how the "custom of the country" in colonial law related to both the involuntary dimensions of servant migration and the term‐bound chattel status that colonial courts imposed on indentured servants. Despite these limitations and the problems associated with his proto‐nationalist framework, the review concludes that Freedom Bound has vastly improved the extant literature on the relationship between the servitude and the ideological, discursive, and labor histories of English colonization.